The addition of dried broccoli (Brassica oleacea L.) leaves can improve the nutrition of noodles. Issue 1 (1st December 2022) - Devi, M; Soekopitojo, S; Putri, A; Pratikto, H; Wibawa, A P; Hamid, M A
Abstract: Broccoli leaves have a high nutritional content so that they can be used as an additional ingredient in noodle products. This study aims to analyze the nutritional content of noodles with the addition of dried broccoli leaves with different percentage ratios. The treated samples were then measured proximately and all the data obtained were analyzed using ANOVA. The result showed that the highest water content, protein content, ash content and fiber content in noodles with the addition of 5% dried broccoli leaves were 39.98% water content, 14.14% protein content, 0.07% ash content and 0.62% fiber content. The highest fat and carbohydrate content in noodles added with dried broccoli leaves is on 3% of the addition. The fat content is 3.56% and the carbohydrate content is 49.56%. These findings indicate that the addition of dried broccoli leaves to noodles increases the nutritional value, especially the fiber and protein content. Broccoli leaves, which have not been used so far, can be used as food ingredients that can increase fiber and protein levels but reduce fat and carbohydrate content in food products with dried broccoli leaves added.